COASTAL MANAGEMENT AND SEA-LEVEL RISE - Pethick J. (My University, 2001)
The predicted rise in sea level due to global warming has given rise to much speculation as to the impact on erosion and accretion rates at the coast as well as increases in hazards to coastal users. This paper focuses on the spatial adjustments that coastal landforms will exhibit in response to changing energy gradients both normal to and parallel to the shore. These adjustments, in many cases, will take the form of the migration of landforms in order that they maintain their position within the coastal energy gradient. Prediction of the rates of such migration will be fundamental to the future management of the changing coastal environment. The paper discusses the impact of sea-level rise on the two basic coastal landform assemblages: those in estuaries and those on the open coast, and then goes on to examine the effect on ebb-tidal deltas that are located at the critical junction between estuaries and open coasts. In each case, the rates of landform migration under an accelerated sea-level rise are predicted and compared with existing rates using examples from the east coast of Britain. Assuming a sea-level rise of 6 mm/year, the paper predicts that estuaries will migrate landwards at rates of around 10 m/year, open-coast landforms can exhibit long-shore migration rates of 50 m/year, while ebb-tidal deltas may extend laterally along the shore at rates of 300 m/year. The implication for the management of such dynamic coastal systems, including such issues as coastal defence and conservation, are discussed.
Keywords: GEOMORPHOLOGY; SEA-LEVEL RISE; ESTUARIES; TIDAL DELTAS; COASTAL MANAGEMENT; COASTAL DEFENCE